Protein Kinase LTRPK1 Influences Cold Adaptation and Microtubule Stability in Rice - Liu, Wei; Ji, Shuxia; Fang, Xiaoliang; Wang, Qingguo; Li, Zhen; Yao, Fangyin; Hou, Lei; Dai, Shaojun (Journal of plant growth regulation, 2013)
Rice LTRPK1, which encodes a member of the casein kinase I family, has been reported to be involved in root development, hormone response, and metabolic processes. Here we further show that LTRPK1 participates in stress resistance by regulating cytoskeleton rearrangement and formation of cold tolerance and adaptation. Semiquantitative RT-PCR analysis revealed enhanced expression of LTRPK1 in plants subject to low-temperature stress at 4 °C, suggesting a role in low-temperature-related cell responses and signal transduction pathways. Further analysis of LTRPK1-deficient transgenic plants showed that under low-temperature treatment, the growth rate of transgenic plant primary roots, which is commonly used as an indicator for cold stress response abilities, was less inhibited than that of control plants. Moreover, damage to the plasma membrane of root cells in LTRPK1-deficient plants was greater than that of controls as measured by relative electrical conductivity (REC). The malondialdehyde (MDA) content of LTRPK1-deficient plants also increased over that of the control, indicating increased plasma membrane permeability. Further immunofluorescence localization observations indicated that microtubules of transgenic plants subject to low temperature disassembled more rapidly, whereas the control plant microtubules in most cells of the root elongation zone kept their normal habitus, which suggested that LTRPK1-deficient plants had reduced capacity to resist low-temperature stress through regulation of microtubule assembly. These results demonstrate involvement of LTRPK1 in low-temperature stress and provide new insight for rice breeding and germplasm innovation to improve crop cold tolerance.